THE INFLUENCE OF WORDWALL LEARNING MEDIA ON STUDENT LEARNING OUTCOMES IN THE 2022/2023 ACADEMIC YEAR OF THE 2022/2023 ACADEMIC YEAR OF STUDENTS' LEARNING OUTCOMES - Ariadi Jimmy; Debora; Ahmad Eko Suryanto (Jurusan Pendidikan Teknologi Dan Kejuruan, 2024)
This research delves into the impact of incorporating Wordwall as a learning tool on the academic performance of students. The study aims to investigate whether the utilization of Wordwall can significantly enhance students' learning outcomes, shedding light on its effectiveness in the contemporary educational landscape. Employing an experimental research design, specifically Quasi Experimental Design with the Nonequivalent Control Group Design model, the research focuses on two variables: the independent variable, Wordwall as a learning medium, and the dependent variable, learning outcomes of grade XI Light Vehicle Engineering students at SMK Karsa Mulya Palangka Raya. The study population encompasses 51 students from classes XI A and B. Nonprobability sampling, using a saturated technique, results in 25 students for the experimental class and 26 for the control class. The research instrument comprises a 44-item learning outcomes test. Data analysis reveals a substantial difference in the average scores for learning outcomes between the experimental (78.24) and control (64.58) groups, with a margin of 13.44. The t-test yields a Sig. (2-tailed) value of 0.000, below 0.05, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). This analysis underscores that the effective implementation of Wordwall as a learning medium significantly improves students' outcomes in light vehicle chassis maintenance and powertrain, surpassing traditional lecture-based models.